Understanding the distinctiveness of Chinese Post-80s tourists through an exploration of their formative experiences - Cheng, Mingming; Foley, C. (Routledge, 2018)
Chinese Post-80s (the Chinese equivalent of Generation Y) are a distinct generation that emerged during a period of rapid political, social and economic change under Deng Xiaoping’s policy exploration with capitalism. Chinese Post-80s demonstrate higher levels of both complexity and sophistication in their tourist behaviours when compared with earlier generations of Chinese tourists yet their distinctiveness has been largely ignored in tourism research. Underpinned by generational cohort theory, this study explores the formative experiences of Chinese Post-80s and provides insights into the way these experiences have shaped this generation and their outbound travel. These formative experiences include Reform and Open Policy, One Child Policy and Education Reforms. Two discrete groups: “made in China” and transnational Chinese Post-80s tourists have been identified. We argue that while Chinese Post-80s tourists may share many aspects in common with their Western counterparts, this generation presents its distinctiveness due to its emergence from a specific sets of events with China’s rapid change that make Chinese Post-80s different from any generation in the global environment, creating new academic inquiries for established theories of generational studies. This nuanced understanding of Chinese Post-80s tourists has profound implications for theory and practice in the context of Chinese outbound travel.